Research on the impact factors of public acceptance towards NIMBY facilities in China - A case study on hazardous chemicals factory. (January 2019) - Li, Wei; Zhong, Huiling; Jing, Nan; Fan, Lu
Abstract: The purpose of this paper is to investigate the factors influencing public acceptance of hazardous chemicals factory in China. By using structural equation modelling approach, perceived risk, perceived benefit, perceived fairness, trust in government and positive affect tag are examined as impact factors. Data is collected from the local public and the general public by internet-based questionnaires. The results show that NIMBY effect is significant to hazardous chemical factory because for the local public who live nearby, perceived risk has the greatest impact on the acceptance, but perceived benefit is not significant, and positive affect tag has significant influence on both perceived risk and perceived benefit. While for general public, perceived benefit is significant to the acceptance, but perceived risk not is statistically significant and positive affect tag influences perceived benefit only. The results also indicate that perceived fairness and trust in government affect the acceptance of both groups, and trust in government affect perceived fairness, perceived risk and perceived benefit. This study contributes to the management of sitting problems of hazardous chemical factory by providing understanding of impact factors on the public acceptance. Recommendations for improving public acceptance are offered at last. Highlights: For the local public, perceived risk has the greatest impact on the acceptance, but perceived benefit is not significant. For general public, perceived benefit is the most significant impact factor influencing the acceptance, but perceived risk is not significant. Perceived fairness and trust in government affect the acceptance of the local public and general public. Trust in government affects perceived fairness, perceived risk and perceived benefit. The public acceptance can be enhanced through the improvement of trust in government and perceived fairness in China.